Composition of Online Shopping Experience: Evidence from India - Gautam, Vikas (Asian Journal of Empirical Research, 2016)
This research was conducted to understand the composition of online shopping experience of Indian consumers. It is very important for marketers to identify and understand the factors of shopping experience before taking any decision. Results of the study showed that website design is the most sought after component by consumers in online shopping followed by perceived benefits, hedonic motivations, perceived risks and psychological factors. Further, results were confirmed using confirmatory factor analysis. The study comprised of 366 respondents.